-10b+3(-1+b)=

Simple and best practice solution for -10b+3(-1+b)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10b+3(-1+b)= equation:


Simplifying
-10b + 3(-1 + b) = 0
-10b + (-1 * 3 + b * 3) = 0
-10b + (-3 + 3b) = 0

Reorder the terms:
-3 + -10b + 3b = 0

Combine like terms: -10b + 3b = -7b
-3 + -7b = 0

Solving
-3 + -7b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -7b = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -7b = 0 + 3
-7b = 0 + 3

Combine like terms: 0 + 3 = 3
-7b = 3

Divide each side by '-7'.
b = -0.4285714286

Simplifying
b = -0.4285714286

See similar equations:

| 8x-5/12=13/18 | | 8(7-p)-8=-16 | | 4x-18+8x=7x+3x+8 | | -3+n=6n+22 | | 3(x-2)=5x+4 | | 1/3x+15=20 | | 4x-2+5x+10+2x+14=0 | | 2x+3=60 | | 2x+5=3x+20 | | -x+11/12=-5/12 | | 1/3(6-15w)=3/8(40w-8) | | -x/2=-6 | | 12y=5y+42 | | 1/2y=1/3y+2 | | 14x+4=9x+7 | | 9y=4y+120 | | 2w^2=-11w-5 | | 6=-2(x+8)-5x | | 4y-(8+2.3y)-x=5+2y | | 9x=-80 | | 220=2(2w-40)+2(w+1) | | -3d-5=28 | | 3513x-4= | | W/4+15=28 | | x^2=3x^2+29 | | 7(1-7x)=-3x-39 | | 3.3-3=15-1.2h | | Y/8+5=-3 | | 45=5x+7(2x-18) | | 45=2x+5 | | 88=4x+4(3x-18) | | -8-8(6n+1)=n |

Equations solver categories